Analysis of the necessity of implementing the "dual specialty" training model from the perspective of nursing master students - Miao-Qing Zhuang; Hong-Fang Chen; Huan-Ze Li (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective is to understand the current situation of clinical practice training for nursing master's degree postgraduates, and discuss the necessity of implementing the "dual specialty" training mode for nursing master's degree postgraduates in China. Methods: Phenomenological research method was used to conduct semi-structured in-depth interviews with 10 nursing master's degree graduates, and the data were analyzed by Colaizzi 7-step analysis method. Results: Four topics were extracted: The objective of clinical practice training for nursing master degree postgraduates was not specific; the cultivation direction is not refined; the ability of clinical practice is weak; the research direction is not consistent with the required position. Conclusion: Implementing special double training mode can solve nursing professional master degree postgraduate education lacking the ability to service the needs of society, graduate students and the existing problems of specialist nurse training and the cultivation of "heavy science, light clinical practice" status quo and the effective way of guiding graduate students career planning, so the implementation of special "double" training mode is necessary.